The nanobiotechnology handbook - Xie, Yubing (CRC Press/Taylor & Francis, 2013)
A thorough overview of nanobiotechnology and its place in advances in applied science and engineering, The Nanobiotechnology Handbook combines contributions from physics, bioorganic and bioinorganic chemistry, molecular and cellular biology, materials science, and medicine as well as from mechanical, electrical, chemical, and biomedical engineering to address the full scope of current and future developments. It includes a companion CD that contains all figures in the book.